Manutenção da prisão preventiva fundamentada na garantia da ordem pública como expressão do autoritarismo no sistema processual penal brasileiro - Passos, Alexandre Veloso dos (2022)
The reality of the Brazilian penal and criminal procedural system demonstrates it as antiquated and undemocratic, risking the freedom and other rights of individuals through the reflection of its authoritarian political-ideological construction. The present work brings a critical analysis of decisions of the Superior Tribunal de Justiça, under the prism of the legal security of the Democratic State of Law, about the maintenance of preventive detention based on the guarantee of public order as an expression of authoritarianism in the Brazilian criminal procedural system. The possibility of determining preventive detention based on the guarantee of public order brings problems in its applicability to the Brazilian criminal procedural system. Faced with a specific and determined conceptual absence for the term "public order", there are wide possibilities of interpretation and definition, resulting in legal uncertainty and reinforcing the trivialization of the use, which should be precautionary, of preventive detention. In this scenario, there is the central problem of the research when examining how the Brazilian criminal procedural system, regarding the application of preventive detention based on the guarantee of public order, achieves legal certainty as a pillar of the Democratic State of Law. To carry out this study, exploratory research with a qualitative approach was used as the basis of this work. We sought to historically analyze, using the instrument of bibliographic review, the normative construction of the Brazilian criminal procedural system, using the political approach and its influence and internal and international confluence in the consolidation of the system. Then, the decision-making legal reality was faced, through an empirical research in the Superior Tribunal de Justiça. From the compilation and analysis of the decisions, it was concluded that authoritarianism is linked to the concept of public order as the basis of preventive detention in the Brazilian criminal procedural system, thus reaching legal certainty as a pillar of the Democratic State of Law